Optical tomography system using digital signal processor: Velocity profile measurement - Ruzairi, Abdul Rahim; Chiam, Kok Thiam; Mohd Hafiz, Fazalul Rahiman; Yvette-Shan Li, Susiapan; Jayasuman, P. (Inderscience Enterprises Limited, 2010)
Link to publisher's homepage at http://www.inderscience.com/